Promoters of Dengue Virus Complete Genome (International Journal of Innovative Research in Computer Science & Technology, 2020)
Present concerning facts of Dengue virus has  proved this as a worldwide emerging threat, which  causes Dengue fever.This is an illness not sufficiently  covered in medical curriculum and there is no  universally acceptable significant diagnostics, vaccines  or treatments of Dengue fever. It has become crucial to  develop a novel, affordable diagnostic tools,  therapeutics and vaccines based on the available  clinical experience Dengue complete genome. The  promoter is one of the regions of DNA sequence where  RNA polymerase first attaches during the initiation of  transcription. For gene expression, the promoter acts as  an important site. There are severe outbreaks of  Dengue in Bangladesh and clearly there is a lack of  sufficient anti-viral drug and vaccine against this virus.  In this research,we have analyzed of all verified Dengue  genome sequences of Bangladesh, available in National  Center of Biotechnology Information (NCBI), USA and  other authenticdatabases, to look for potential  promoters for vaccine and therapeutic applications.
Keywords: Dengue fever; dengue virus (DenV); promoter; bioinformatics; NCBI; Bangladesh